CAN WE OVERCOME THE ‘MIND-BODY’ DUALISM? (SOME MODERN PHILOSOPHICAL THEORIES) (Annual of the Faculty of Philosophy in Skopje, 2009)
This text analyses several theories that have been trying to answer a philosophical question that has existed for centuries.The ‘mind-body’ dualism is a challenge for many authors. There are numerous theories, the advocates of which claim that each offers solution to this problem. However, none of these theories is without shortcomings. The author of this text is trying to analyse several contemporary theories that see the solution of the problem of dualism between the body and the mind within the meta-language and the theory of identities. The text offers the views of Michael Arthur Simon, J.J. Smart and Thomas Nagel. Considering Simon’s theories and the views of other authors, Vladimir Davcev aims to show how modern philosophical thought deals with this everlasting problem, and whether and how much has been achieved to overcome it.
Keywords: dualism; introspection; mind; physicalism; theory of identity